2019
DOI: 10.2134/agronj2019.02.0108
|View full text |Cite
|
Sign up to set email alerts
|

Fertilizer Placement Affects Corn and Nitrogen Use Efficiency in a Claypan Soil

Abstract: Agronomic efficiency (AE) and apparent N recovery efficiency (RE) can be improved by developing more effective N fertilizer placement strategies; however, minimal research has focused on poorly‐drained claypan soils which are prone to saturated conditions and gaseous N loss. The objective of this 2‐yr study was to determine the effectiveness of different N fertilizer placement methods on corn (Zea mays L.) grain yield, grain quality, silage yield, N uptake, AE, RE, and spatial soil N distribution over time. Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…In addition to drying and wetting cycles, soil pH also had an important role in regulating urea hydrolysis, nitrification, and denitrification, which can affect N 2 O emissions (Cabrera et al, 1991; Dancer et al, 1973; Van den Heuvel et al, 2011). Soil pH of the study site in 2017 varied between 6.7 and 5.3 for depths of 0 to 61 cm among treatments (Steusloff et al, 2019). Van den Heuvel et al (2011) reported that NO 3 − production in low pH soils was reduced and resulted in buildup of N 2 O in soil that contributed to higher emissions of N 2 O at soil pH of 5.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to drying and wetting cycles, soil pH also had an important role in regulating urea hydrolysis, nitrification, and denitrification, which can affect N 2 O emissions (Cabrera et al, 1991; Dancer et al, 1973; Van den Heuvel et al, 2011). Soil pH of the study site in 2017 varied between 6.7 and 5.3 for depths of 0 to 61 cm among treatments (Steusloff et al, 2019). Van den Heuvel et al (2011) reported that NO 3 − production in low pH soils was reduced and resulted in buildup of N 2 O in soil that contributed to higher emissions of N 2 O at soil pH of 5.…”
Section: Discussionmentioning
confidence: 99%
“…Soil samples to a depth of 61 cm from all treatments were collected on 10 July 2017 (data not shown). The DB+NI treatment had 7 to 10 mg kg −1 greater NO 3 –N in soil at the 15‐cm depth compared with all other treatments, which could explain higher N 2 O losses later in the season (Steusloff et al, 2019). Additionally, higher N 2 O loss from IA and SA early in the growing season was probably due to greater NO 3 − substrate left in the soil for IA and SA, which might have been reduced in concentrations which resulted in lower N 2 O fluxes later in the season from these treatments (Steusloff et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to N application timing, fertilizer N placement strategies may improve crop yields and N use efficiency in claypan soils. Many studies have shown lower grain yields and N uptake with a surface broadcast N application compared to incorporated band N placement [6,[15][16][17]. Other studies did not observe any advantages of subsurface band placement of urea ammonium nitrate (UAN) over surface broadcast placement [8,18].…”
Section: Introductionmentioning
confidence: 99%